(untitled) (diségno, 2024)
As often happens at the end of a deeply engaging effort, professor Adriana Rossi, has developed a keen sensitivity towards her subject of study which was also the aim of a previous research [Rossi 2014]. The acquired experience has thus become both a stimulus and a tool for further exploration. The book is the result of a new work, and it has been completely rewritten according to the author’s own words. The text, published in December 2023 with the invaluable collaboration of Pedro Cabezos, publicly presents digital representations developed during a joint research project conducted in 2016 at the University of Campania [1]. [read more]